Relationship between seismic acoustic impedance (AI) and total organic carbon (TOC) content: a case study from Australia - MUHAMMAD RIDHA ADHARI; MUHAMMAD YUSUF KARDAWI (Jurnal Natural, 2023)
. Shale gas has become of interest of geoscientists globally because of its potentials to expand our energy supply. This research used well logs data and total organic carbon (TOC) data from Perth and Canning Basins, Australia. The objective of this research is to investigate source rock potential of the study area by examining the relationship between TOC content and seismic acoustic impedance (AI) derived from well log data, using regression analysis. The outcomes of this research show that for claystone/siltstone, the relationship between AI and TOC is nonlinear, while for shale the correlation is linear. However, there is no fixed equation that can be used as a standard for this linear/nonlinear relationship. Results show that for a certain type of lithology, the relationship between TOC and AI is different for different formations. This is interpreted to be caused by different depositional environment, diagenesis, mineralogical composition and different depth of burial. Findings of this study are expected to provide some new insights into the relationship between AI and TOC for various types of lithology and contribute to shale gas exploration studies.